Beneficial effects of neuronal ATF6 activation in permanent ischemic stroke - Li, Xuan; Li, Ran; Lu, Liping; Dhar, Ashis; Sheng, Huaxin; Yang, Wei (Frontiers in Cellular Neuroscience, 2022)
Objective: Brain ischemia leads to the accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER) lumen and consequently, ER stress. To help cells restore ER function, a series of adaptive stress response pathways, collectively termed the unfolded protein response (UPR), are activated. We have previously demonstrated that the UPR pathway initiated by ATF6 is pro-survival in transient ischemic stroke. However, the effect of ATF6 activation on outcome after permanent ischemic stroke remains unknown. Here, we addressed this knowledge gap. Methods: sATF6-KI mice with functional short-form ATF6 (sATF6) predominantly expressed in forebrain neurons were subjected to 2 ischemic stroke models: photothrombotic stroke and permanent middle cerebral artery occlusion (pMCAO). Both short-term and long-term functional outcomes were assessed. Changes in neuroinflammation and cerebrovascular density after pMCAO were also assessed. Results: Compared to littermate controls, sATF6-KI mice performed significantly better in open field, cylinder, and foot fault tests on day 1 or 3 after photothrombotic stroke. However, on days 7 and 14 after stroke, performance of these functional tests was not significantly different between groups, which is likely related to mild brain damage associated with this stroke model. Thus, to evaluate long-term effects of ATF6 activation in permanent stroke, we turned to our pMCAO model. We first found that on day 4 after pMCAO, functional outcome was better, and infarct volumes were smaller in sATF6-KI mice vs controls. Next, the 15-day stroke outcome study indicated that compared to control mice, sATF6-KI mice consistently exhibited improved performance in neurologic scoring, tight rope test, and tape removal test, after pMCAO. Moreover, sATF6-KI mice showed higher vascular density and lower activation of both astrocytes and microglia around stroke regions on day 16 after pMCAO. Conclusions: Here, we presented the first evidence that activation of the ATF6 UPR branch is protective in permanent ischemic stroke, which further supports the therapeutic potential of targeting the ATF6 pathway in stroke.